Child Bride Reflected In Khaled Hosseini's A Thousand Splendid Suns Novel (2007): A Feminist Approach - Pramesti, Ferdilla Hana; , Dr. Phil. Dewi Candraningrum, S. Pd, M. Ed; , Drs. Abdillah Nugroho, M.Hum (2013)
The major problem of this study is how child bride is reflected in A Thousand Splendid Suns novel by Khaled Hosseini. The objective of this study is to analyze the novel based on its structural elements and to analyze the novel based on the feminist analysis. In analyzing A Thousand Splendid Suns the writer uses descriptive qualitative method and feminist approach. The data sources consist of primary data and secondary data sources. The primary data source is A Thousand Splendid Suns novel and the secondary data sources are the other sources related to the analysis such as books of literary theory, the author‟s biography, the information of Kabul city and the other relevant information to analyze this research. The method of the data collection is library research. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusions. First, from the structural analysis of the novel, it shows that Khaled Hosseini wants to illustrate his idea about women that live based on the social background in Afghanistan. Second, from the analysis of the structural elements of the novel, Hosseini makes the elaborations of the structural element into good in unity. They are namely character and characterization, setting, plot, style, point of view that related to build the theme of the story that to show up the power of woman in a bad condition. Therefore, the story of child bride in Khaled Hosseini‟s A Thousand Splendid Suns novel can be analyzed by using Feminist Approach. Child bride is the result of patriarchal culture.